2020
DOI: 10.34172/ijhpm.2020.243
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pharmacovigilance System in Iran

Abstract: Background: Evaluating a pharmacovigilance system helps identify its deficiencies and could facilitate measures to remedy and improve the quantity and quality of adverse drug reaction (ADR) reports and other opportunities for pharmacovigilance systems strengthening. This study aimed to evaluate the status of pharmacovigilance in Iran using the World Health Organization (WHO) pharmacovigilance indicators with the prospect of identifying the gaps and areas for improvement. Methods: This study was conducted in 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…A detailed description of study methodology has been previously reported [23,28]. The following provides a summary with relevant additional detail as needed.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of study methodology has been previously reported [23,28]. The following provides a summary with relevant additional detail as needed.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the researches done regarding evaluationknowledge, attitude and performance of pharmacovigilance system. Meanwhile, the existence of a drug monitoring system has led to the improvement of the quality and quantity of drug side effect reports and provides more accurate decision-making in this eld [11].Around the world voluntary reporting systems have been working in the eld of pharmacovigilance for over forty years. Along with the activities carried out in many countries, also in Iran, the National Center for Registration and Investigation of Adverse Drug reactions is responsible for organizing the activities of adverse drug reactions and also to collect and review the reports at the national level.…”
Section: Introductionmentioning
confidence: 99%
“…In 1997, the rst cases of drug side effects were sent to the newly established ADR center of the country, and in 1998, Iran joined the WHO international program [12]. The Center for Registration and Investigation of Adverse Drugs, as the only national center in the country, collects and registers reports of drug side effects observed by the medical community in order to collect adverse drug reactions reports, according to international standards, yellow forms (Yellow card) has been prepared by this center [11].…”
Section: Introductionmentioning
confidence: 99%
“…An AEFI can be any unfavorable or unintended sign, abnormal laboratory finding, symptom or disease. Pharmacovigilance has a low priority in developing countries [ 16 ] such as Iran, where the status of pharmacovigilance is unclear [ 17 ]. Therefore, more studies on recognizing and reporting AEFIs are needed in these countries to guide legislators and patients in addressing their concerns about the safety of vaccines.…”
Section: Introductionmentioning
confidence: 99%